Fiscal consequences of corporate tax avoidance - Katarzyna Bilicka; Evgeniya Dubinina; Petr Janský (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
Multinational corporations shift a large share of their foreign profits to tax havens and, due to this corporate tax avoidance, governments worldwide lose a portion of their tax revenues. In this paper we study the consequences of multinational tax avoidance for the structure of government tax revenues. First, we show that, at the country level, countries with large revenue losses due to profit shifting have lower corporate tax revenues and rates. At the same time, they raise a larger share of tax revenues from personal and indirect taxes and have higher indirect tax rates. Second, to establish causality, we use German municipal data and analyse the effects of changes in municipal tax rates levied on corporate profits on local tax revenue structure. We show that following a tax rate increase, municipalities with a large presence of aggressive multinational corporations experience a significant decline in that tax revenue share.
Keywords: E62; H26; H71; 330; corporate tax avoidance; profit shifting; multinational corporations; tax revenue structure